2020
DOI: 10.1155/2020/4038305
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Traffic Simulation Calibration Level for Reliable Estimation of Vehicle Emissions

Abstract: Vehicle emissions are largely determined by the details of driving behaviours. Accordingly, emissions are often estimated by integrating micro-scale emission models into traffic simulations. Under this approach, it is essential to replicate the actual traffic situation being considered in an emission evaluation using a proper calibration procedure. Most previous research with respect to traffic flow has primarily focused on adjusting the complex combinations of parameters evaluated in these models, but it is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Three measures of MAPE, RMSPE, and the GEH statistic have been estimated to be 0.0001, 0.0153, and 0.7849, which satisfy the acceptance levels. Note that the acceptance levels of the measures are 0.05, 0.05, and 5, which are considered to be reasonable in the simulation ( 19 , 20 ), respectively. The validation results have shown the measures to be 0.0330, 0.0368, and 0.7190, respectively, which are all within the acceptance levels.…”
Section: Building Driving Behavior Models and Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Three measures of MAPE, RMSPE, and the GEH statistic have been estimated to be 0.0001, 0.0153, and 0.7849, which satisfy the acceptance levels. Note that the acceptance levels of the measures are 0.05, 0.05, and 5, which are considered to be reasonable in the simulation ( 19 , 20 ), respectively. The validation results have shown the measures to be 0.0330, 0.0368, and 0.7190, respectively, which are all within the acceptance levels.…”
Section: Building Driving Behavior Models and Applicationmentioning
confidence: 99%
“…Maheshwary et al calibrated the VISSIM parameters using multiple linear regressions and GA and demonstrated its validity with respect to different flow conditions ( 18 ). Kim et al ( 19 ) and Mahmood and Kianfar ( 20 ) examined which measures are appropriate in microscopic traffic simulation. The studies above have proved the strength of the microsimulation tools for various traffic conditions.…”
mentioning
confidence: 99%
“…The results showed that the operational performance of roundabouts could be significantly affected by the percentage of heavy vehicles. Kim et al [30] proposed a systematic guideline that could be used for calibrating reliable microscale estimates of vehicle emissions. The VISSIM environment was used to simulate the traffic flow.…”
Section: Detailed Review Of the Collected Studiesmentioning
confidence: 99%
“…Traffic simulations are categorised by level of detail into three separate categories 15 . First, the most precise information on each vehicle in the system is microscopic simulations 16 .…”
Section: Introductionmentioning
confidence: 99%